Projekt Logiki Infinitarnej Ernsta Zermela - Pogonowski, Jerzy (Investigationes Linguisticae, 2007)
This paper is a summary of a more comprehensive work Infinitarna Logika Ernsta Zermela (The Infinitary Logic of Ernst Zermelo) being currently under preparation for the research grant KBN 2H01A 00725 Metody nieskończonościowe w teorii definicji (Infinitary methods in the theory of definitions) headed by Professor JANUSZ CZELAKOWSKI at the Institute of Mathematics and Information Science of the University of Opole, Poland. The presentation of Zermelo's ideas is accompanied with some remarks concerning the development of infinitary logic.